Intersocietal survey on real-world asthma management in Italian children - Maria Angela Tosca; Antonio D'Avino; Giuseppe Di Mauro; Gian Luigi Marseglia; Michele Miraglia del Giudice; Giorgio Ciprandi; SIAIP Delegates; FIMP Delegates (BMC, 2024)
Abstract Pediatric asthma management is a compelling challenge for every pediatrician. Different aspects require attention and definition. The present Intersocietal Survey aimed to collect real-world experiences from a sample of Italian pediatricians. A web platform was used to collect anonymous answers to the survey questions. Four hundred four pediatricians participated in this initiative promoted by the Italian Society of Pediatric Allergy and Immunology (SIAIP), the Society of Preventive and Social Pediatrics (SIPPS), and the Federation of Italian Pediatricians (FIMP). The results showed an extensive participation of primary care pediatricians (72%). There was a large consensus about diagnostic criteria and medication choice. However, treatment duration and device choice were various. Adherence to guidelines on general aspects of practical clinical management was high. In conclusion, the present Intersocietal Survey confirmed that pediatric asthma management is rather satisfactory, even if further improvement should concern a more widespread use of ICS for acute asthma/wheezing attacks, a better definition of the duration of ICS and bronchodilator use, and hospital-primary care integration.